Associations between neuroanatomy and neurophysiology with turning performance in people with multiple sclerosis - Swanson, Clayton Winford, author; Fling, Brett W., advisor; Leach, Heather J., committee member; Stephens, Jaclyn A., committee member; Mancini, Martina, committee member; Miravalle, Augusto A., committee member (Colorado State University. Libraries, 2021)
Neurodegenerative diseases such as multiple sclerosis (MS) are associated with decreased mobility and a variety of changes affecting neural structure and function. Due to the cortical influence on various aspects of mobility, it is likely that these neural adaptations negatively affect mobility, and therefore, increase the potential for falls. Additionally, the progression of MS has been associated with cortical grey matter atrophy, and adaptions to neurophysiological activity. While previous research has demonstrated associations between levels of inhibition and a variety of turning characteristics in neurotypical young and older adults, it remains unclear if associations exist between cortical structure and function for dynamic lower limb control for daily tasks such as turning. Therefore, purpose of this project was to understand how sensorimotor cortical thickness and corticospinal excitation and inhibition contribute to turning performance in both people with MS (PwMS) and age-matched neurotypical control (HC) participants. Participants were asked to conduct a series of 360˚ in-place turns at two self-selected speeds and 180˚ turns during a self-selected pace two-minute walk test. Quantification of turning was assessed using wireless inertial sensors placed on each foot, around the waist, on the sternum, and on the forehead. Grey matter (GM) thickness of the sensorimotor cortex (i.e., pre-, para-, and postcentral gyri) was measured via magnetic resonance imaging (MRI) and processed using FreeSurfer 6.0.0 (http://surfer.nmr.mgh.harvard.edu/, Harvard University, Boston, MA, USA). To measure corticospinal excitation and inhibition single-pulse transcranial magnetic stimulation (TMS) was performed. The leg region of both motor cortices was identified by acquiring the resting motor threshold (RMT) of the tibialis anterior. To assess neurophysiology, participants sustained an isometric contraction in dorsiflexion at 15% of their maximal voluntary contraction for three-minutes. Simultaneously, a TMS stimulation was delivered at 120% of RMT every 7-10 seconds. This procedure was conducted for both cortical hemispheres. A total of forty-nine individuals (23 HC, 26 MS) participated in the study. PwMS demonstrated reduced turning performance for a variety of 360˚ turning variables, although only one variable was significant between groups for the 180˚ turns. GM thickness revealed significant cortical thinning of the pre- and paracentral gyri in the MS group, while the postcentral gyrus did not demonstrate between group differences. For TMS measures, PwMS demonstrated reductions in excitation and inhibitory capacity compared to neurotypical controls. All significant correlations were primarily observed in the MS group and demonstrated lateralization, such that they were limited to the left hemisphere. The current results showed that both cortical thickness and inhibitory activity were associated with turning performance in PwMS, but not in the HC group. The associations between inhibitory activity and turning performance were stronger than the associations between cortical thickness and turning performance. These results may indicate that inhibitory activity is more associated with dynamic lower limb movements compared to GM thickness. Furthermore, these results suggest that PwMS may rely on different neural resources to perform dynamic movements typically associated with fall risk.
Keywords: mobility; transcranial magnetic stimulation; magnetic resonance imaging; turning; multiple sclerosis